Non-DAC Donors: A Better Alternative or Rather Corruption Stimulants? - ElZakzouk, Farida Ehab (AUC Knowledge Fountain, 2023)
Foreign development aid has for long been part of many aid receiving countries’ development agendas in hope of it assisting their economic and social development plans. For decades the traditional development aid providers, who are members of the OECD and are known as DAC donors, have been criticized for not specializing and instead fragmenting their donations hence leaving space for corrupt officials in the receiving countries to exploit the donations. Recently, a new type of donors has emerged, who are not part of the OECD. The emergence of these new donors, known as non-DAC donors, makes us, as political scientists ponder, could these newly emerged type of donors serve as a better alternative than the traditional DAC donors, or are they equally poor, if not worse? The newly emerged non-DAC donors are being highly criticized due to the non-selectivity of their aid and due to not attaching to their aid any conditionalities related to good governance. This dissertation aims to explore whether therefore we could empirically demonstrate that countries receiving more development aid from non-DAC donors than DAC donors could over time be characterized with higher levels of corruption. This study utilizes a quantitative approach to establish whether in fact a positive correlation between non-DAC development aid and high corruption levels exists. Additionally, it aims to explore whether non-DAC development aid, in comparison to DAC development aid, is characterized with higher levels of corruption.